Effects of Climate Change on Fluted Pumpkin Production and Adaptaton Measures Used Among Farmers in Rivers State - C C Ifeanyi-obi; C C Asiabaka; E Matthews-Njoku; F N Nnadi; A C Agumagu; O M Adesope; F O Issa; R N Nwakwasi (Journal of Agricultural Extension, 2014)
The importance of fluted pumpkin crop in rural household economy cannot be over emphasized. Farmers in the South South Nigeria depend greatly on fluted pumpkin for its many uses. The production however is beset with a myriad of constraints of which climate change is one of the most outstanding. The study assessed the effects of climate change and adaptation measures used by fluted pumpkin farmers in Ikwerre Local Government Area(LGA) of Rivers State, Southsouth Nigeria. Multi-stage sampling technique was used to select respondents for the study. Out of the twelve communities that make up Ikwerre LGA, six communities were randomly chosen from which one hundred and eighty fluted pumpkin farmers were proportionately selected. Interview schedule and focus group discussion were used to elicit in depth information from respondents. Data were analyzed using percentage, frequency count and mean. Tables and charts were used in presentation of data. The result of the study showed that 51 percent of the respondents were female, majority were married (77 percent) and were full time farmers (79 percent). Relatively large proportion had no formal education (42 percent) and indicated both consumption and sale (79 percent) as the major aim of production. The respondents perceived that unpredictable climate condition, changes in rainfall pattern, changes in rainfall distribution, reduced yield of fluted pumpkin and reduction of family income were the major effects of climate change on fluted pumpkin production. A combination of fluted pumpkin production with other income generating activities was shown to be the most widely used adaptation strategy by respondents. Based on the results of the study it was recommended that improved extension services that can provide the needed farming inputs (fluted pumpkin seedlings, fertilizers e.t.c) as well as useful and relevant information on climate change and adaptation strategies should be made available to the people.